Design of composite structures for minumum weight - Akbulut, Mustafa. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
The goal of this study is to develop methodologies to optimize the structural design of composite materials to achieve the minimum weight. Mainly three different problem areas were considered. Firstly, weight minimization of laminated composite plates subjected to in-plane loading; secondly, as an extension of the first problem, weight minimization of laminated composites subjected to in-plane and out-of-plane loads; thirdly, optimal design of laminated composite plates with notches using progressive failure approach. Considering that composite materials are generally used in applications where weight is critical and considering their high cost, in this study, designs with minimum material use were aimed. Fiber orientation angle and number of plies in each lamina were used as design variables. The maximum stress and Tsai-Wu criteria were used individually or together to predict static failure. Different geometries and loading conditions were considered. Because the problems considered in this study contain numerous local optimums, a global search algorithm, Simulated Annealing, was used as the optimization algorithm. A number of modifications were proposed to improve the reliability of the algorithm.
Keywords: Composite construction.; Lightweight construction.